2002
DOI: 10.1016/s0008-6363(01)00435-7
|View full text |Cite
|
Sign up to set email alerts
|

The effect of preconditioning (ischemic and pharmacological) on myocardial necrosis following coronary artery bypass graft surgery

Abstract: Ischemic preconditioning is superior to the other techniques at limiting myocardial necrosis during CABG. Pharmacological preconditioning may confer some benefit but this was not statistically shown using a specific adenosine A1 agonist (GR79236X).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
46
1
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(48 citation statements)
references
References 39 publications
0
46
1
1
Order By: Relevance
“…Another study (170) acquired evidence of exaggeration of injury with ischemic Precon. Subsequent work by Teoh and colleagues (214,215) indicates a superior protection with ischemic Precon vs. intermittent cross-clamping, cold cardioplegia, or pharmacological Precon, with 50 -70% reductions in troponin T release compared with these interventions. Others present evidence that ischemic Precon is superior in limiting markers of cardiac cell damage vs. intermittent cross-clamp fibrillation (100,207).…”
Section: Clinical Application Of Precon and Postconmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study (170) acquired evidence of exaggeration of injury with ischemic Precon. Subsequent work by Teoh and colleagues (214,215) indicates a superior protection with ischemic Precon vs. intermittent cross-clamping, cold cardioplegia, or pharmacological Precon, with 50 -70% reductions in troponin T release compared with these interventions. Others present evidence that ischemic Precon is superior in limiting markers of cardiac cell damage vs. intermittent cross-clamp fibrillation (100,207).…”
Section: Clinical Application Of Precon and Postconmentioning
confidence: 99%
“…Indeed, one of the aims of ongoing research into the molecular bases of these responses is to identify candidates for pharmacological manipulation. While Teoh et al (214) acquired evidence of a superior effect of ischemic vs. pharmacological Precon, other support for benefit via conditioning pharmacomimetics has been acquired. Adenosine may play a key role in triggering cardioprotection with Precon and Postcon (77,231), although it provides other beneficial effects that may be independent of these responses (166).…”
Section: Clinical Application Of Precon and Postconmentioning
confidence: 99%
“…An elegant model of ischemic preconditioning is restricted to patients undergoing coronary artery bypass surgery. 37 This limitation hinders efficient screening of pharmacological or physiological interventions for their potential to interfere with ischemic preconditioning in conscious persons. In contrast to the limitations of these methods, ischemic forearm exercise followed by Annexin A5 scintigraphy is not biased by collateral circulation, detects membrane changes that directly result from ischemiareperfusion injury, and can easily be applied to volunteers with minimal risk of serious complications.…”
mentioning
confidence: 99%
“…9 Possibly the most direct evidence for the occurrence of preconditioning in humans comes from studies in patients undergoing coronary artery surgery, where it has been shown that the introduction of two 3-minute periods of global ischemia early in the operation reduced the loss of high energy phosphates 10 and troponin T after the subsequent prolonged period of ischemia during the fashioning of the coronary graft anastomoses. 11,12 Thus, overall, the available evidence supports the notion that preconditioning not only occurs in humans but does so within context of clinical procedures and as such may be of potential benefit to patients.…”
Section: See P 3091mentioning
confidence: 62%